The importance of internal auditing in the decision-making process (an exploratory study of the opinions of a sample from the technical colleges complex at Sulaimani Polytechnic University) - محمد, پەیمان ڕفیق; فتاح, ناجی افراسیاو (Sulaimani Journal for Humanities, 2019)
Internal audit plays an important role as one of the main pillars that seek to provide reliable and correct information to managers at all administrative levels in order to arrive at the appropriate and timely decision. Therefore, this process is considered one of the most difficult responsibilities in the institutions in light of the economic conditions that are dynamic and in crisis and financial scandals. Therefore, financial decision makers should rely on internal audit reports. This study aimed at identifying the role and importance of internal auditing in decision making in the institutions under study, on this basis, the Technical College Campus of Sulaymaniyah Technical University was chosen to prove its validity. The study has reached to a number of results, the most important of which are: The most personal factors influencing the role of the internal auditors are their continuous qualifications. There is weakness in the auditors' understanding of their role in the institution and their ability to accomplish the tasks assigned to them. Which prevent their effective participation in the decision-making process . Based on the results obtained, a number of recommendations were proposed. The most important of these recommendations are: Institutions should make the internal auditors sense the effective role that the auditing profession can play in minimizing negative practices and fraud which positively affects the decision making process, considering internal auditing to be a mean which it is aim is to watch employee’s behavior within institution, practitioners must put the public interest above all considerations away from dependence on management.